Testing to Failure of a 55-year-old Prestressed Concrete Bridge in Kiruna : Bending, Shear and Punching of Girders and Slab. Fracture Properties of Materials. Test Results, Modelling and Assessment. Final Report BBT 2017-030 - Nilimaa, Jonny; Nilforoush, Rasoul; Bagge, Niklas; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och brand, 2020)
Results are presented from the testing to failure of a 55-year-old prestressed concrete bridge with five continuous spans and a total length of 121.5 m. The bridge was situated in Kiruna in northern Sweden. Results are given from load, deflection and strain measurements during bending-shear tests of the girders and from a punching test of the slab. The testing was carried out in June 2014. Extensive assessment and modelling of the bridge with finite element methods have taken place and is summarized. The strength of the bridge was much higher than what could be found with ordinary code methods. The advanced non-linear models were, after calibration, able to predict the behaviour in a good way. In numerical assessments of concrete bridges, the value of the concrete tensile strength fct and the fracture energy GF plays an important role. However, mostly these properties are only estimated based on the concrete compressive strength using empirical formulae. In order to study methods to determine the concrete tensile strength and fracture energy for existing bridges, tests were carried out in 2019 on notched cylindrical concrete cores drilled out from the Kiruna Bridge. Different methods to determine the concrete fracture energy are discussed and recommendations are given for assessment procedures. There are also Appendices A-F of 109 pp BBT 2017-030